Possible liquid electrolytes for fluoride ion batteries - Tay, Jasmine Jia Wen. (2013)
While lithium ion batteries have been commercialized and used in everyday electronics for the last 22 years, its cell life and thermal stability issues hinder the use of lithium ion batteries in larger scale applications such as the automotive and aerospace industries. Instead, the substitution of lithium ion charge carrier with fluoride ions presents itself as a promising alternative to the highly reactive lithium. Also the properties of ionic liquids are also considered in both lithium and fluoride ion battery applications as alternative electrolytes. Therefore, the possibility of using ionic liquids and fluoride ion charge carrier is explored in this report. Solubility of alkali fluorides in three perfluorinated ionic liquids and common organic solvents, including the effect of adding cation specific crown ethers, are studied. Alkali fluorides are found to exhibit low solubility with low concentrations possible with the aid of crown ether. Also, the electrochemical stability of these solutions are measured and compared to pure ionic liquids and existing lithium ion battery benchmarks, showing good comparison. Finally, conductivity of solutions measured showed variation in solutions with their respective constituents, according to literature, providing conclusive results on the possible electrolyte composition to be used for fluoride ion batteries.